Influence of organic acids and heat treatment on ginsenoside conversion - Gwi Yeong Jang (Journal of Ginseng Research, 2018)
Background: Heat treatments are applied to ginseng products in order to improve physiological activities through the conversion of ginsenosides, which are key bioactive components. During heat treatment, organic acids can affect ginsenoside conversion. Therefore, the influence of organic acids during heat treatment should be considered. Methods: Raw ginseng, crude saponin, and ginsenoside Rb1 standard with different organic acids were treated at 130°C, and the chemical components, including ginsenosides and organic acids, were analyzed. Results: The organic acid content in raw ginseng was 5.55%. Organic acids were not detected in crude saponin that was not subjected to heat treatment, whereas organic acids were found in crude saponin subjected to heat treatment. Major ginsenosides (Rb1, Re, and Rg1) in ginseng and crude saponin were converted to minor ginsenosides at 130°C; the ginsenoside Rb1 standard was very stable in the absence of organic acids and was converted into minor ginsenosides in the presence of organic acids at high temperatures. Conclusion: The major factor affecting ginsenoside conversion was organic acids in ginseng. Therefore, the organic acid content as well as ginsenoside content and processing conditions should be considered important factors affecting the quality of ginseng products. Keywords: ginseng, ginsenoside conversion, heat treatment, organic acids, thermal stability